PELAKSANAAN PRINSIP KEHATI-HATIAN DALAM PEMBERIAN FASILITAS KREDIT KEPADA NASABAH PAYROLL PT BANK MANDIRI YOGYAKARTA - HINDRIYANI, LINDA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Objective of this research was to identify implementation of carefulness principles by bank in credit agreement without collateral given to payroll customers. It was also to identify resolution when there is bad debt at payroll customers in PT Bank Mandiri. It is descriptive analytical research with normative research type. The research used juridical normative approach supported with secondary data. It used qualitative analysis to analyze and process collected data. The result indicated that channeling credit without collateral to payroll customer was done by Bank Mandiri with carefulness principles. Assessment and analysis was done in deep way on aspects of the credit known as the five C’s of credit. Resolution when there is bad debt on payroll custom in PT Bank Mandiri was done with following ways. Customers that did not pay fund till one billing month, officer will visit customer office to collect the fund. When after collection in the office, the fund is not paid the bank wait till next month. If until twice debiting the fund is not sufficient, Bank Mandiri through collection department will do continuously collection to customers.